Electrical system with distributed generation of radio center with abruptly variable nature of load - B. A. Kosarev; S. V. Krivaltsevich; A. A. Ohotnikov; V. K. Fedorov (Омский научный вестник)
In this work using the example of a radio center the issue of organizing an electrical system with distributed generation of a consumer with a sharply variable nature of the load is considered. The creation of electrical complexes based on distributed energy generation is a promising direction in the development of energy. One of the problems that can be solved using distributed generation is the smoothing the power profile of the consumer. The purpose of the research work is to study the features of the organization of an electrical system with distributed generation of a radio center with a sharply variable nature of the load. When constructing structural diagrams of the power supply system of the radio center, the fundamentals of power supply of industrial enterprises are used. Recommendations on the technical parameters of power plants are integrated based on the results of research in the field of distributed power generation and related regulatory documents and radio communication systems. Based on the results of the research work, the technical characteristics of power plants are noted, which should be paid attention to when designing an electrical system with distributed generation of a radio center. Variants of the structural diagram of the electrical system with distributed generation of the radio center and the corresponding power distribution schemes are proposed.